Characterizing Types of Readmission After Acute Coronary Syndrome Hospitalization: Implications for Quality Reporting. Issue 5 (18th September 2014) - Southern, Danielle A.; Ngo, Jennifer; Martin, Billie‐Jean; Galbraith, P. Diane; Knudtson, Merril L.; Ghali, William A.; James, Matthew T.; Wilton, Stephen B.
Abstract : Background: Thirty‐day readmission rates have been tied to hospital reimbursement in the United States, but remain controversial as measures of healthcare quality. We profile the timing, main diagnoses, and survival outcomes of inpatient and emergency department readmissions after acute coronary syndrome (ACS), based on a large regional database. Methods and Results: Patients enrolled in the Alberta Provincial Project for Outcomes Assessment in Coronary Heart Disease (APPROACH) registry with an ACS hospitalization between April 2008 and March 2010 (n=3411) were included. Primary outcomes were inpatient and emergency department–only readmissions, at 30 days and 1 year. Predictors of 30‐day readmission were identified, and the association between 30‐day readmission status and mortality was evaluated. A total of 1170 (34.3%) patients had ≥1 hospital readmission within 30 days, reaching 2106 (61.7%) within 1 year of ACS discharge. Of first readmissions, 45% were emergency department only and 53% were for cardiovascular or possibly related diagnoses. Renal disease and diabetes predicted all‐cause readmissions at 30 days and 1 year, but there were no robust predictors of cardiovascular readmissions. Thirty‐day inpatient, but not emergency department, readmissions were associated with increased mortality. Conclusions: Hospital readmissions within 30 days after discharge for ACS are common, and associated with increased mortality. However, our findings underline that readmissions are quite heterogeneous in nature, and that many readmissions are unrelated to index stay and thus not easily predicted with common clinical variables. All‐cause 30‐day readmission rates may be too simplistic, and perhaps even misleading, as a hospital performance metric.